👤

1. Zapisz sumy jednomianów podobnych w prostszej postaci.
a) 6xy – 5xy + 4xy – 3xy + 2xy - xy =
b) 2,5a - a - 4a +6,5a - 3,5a =
c) 0,3x – 0,4x + 0,5x – 0,6x + 0,7x =
=
d) 696y – 969y+ 69y - 96y =
e) ja2 + a2 + a2 - 2a2 =


Odpowiedź :

Odpowiedź:

a)3xy; b)5,5a c)0,5x d)0 e)a2

Szczegółowe wyjaśnienie:

Jeśli w pkt e -lwartośc "ja2"nie jest pomyłką to wynik będzie równy ja2

a) 6xy – 5xy + 4xy – 3xy + 2xy - xy = 3xy

b) 2,5a - a - 4a +6,5a - 3,5a = 0,5a

c) 0,3x – 0,4x + 0,5x – 0,6x + 0,7x = 0,5x

d) 696y – 969y+ 69y - 96y = -300y

e) [tex]ja^2 + a^2 + a^2 - 2a^2 = a^2j + a^2 + a^2 - 2a^2 = a^2j[/tex]